Security in cloud computing using firewall - Langote, Abhishek; Dalal, Omkar; Kharade, Jyoti (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is more popular these days, and the number of its users is increasing hence the security issues are also increasing. Cloud Computing is a relatively new concept that presents a good number of benefits for its users; however, it also raises some security problems which may slow down its use .The biggest issue in the cloud computing is security. This paper discuss about cloud service model, security issues in cloud computing. There are some security challenges like data security, network security and data transmission. Paper discuss about them and types of firewalls and how to implement firewall in the system that will help in cloud security